"We're looking out through a window to a field of weeds and sand and stones": The Stadium Broadcast, a Radio Memorial. Issue 4 (November 2019) - Joyce, Zita
This article explores the scope of small-scale radio to create an auditory geography of place. It focuses on the short-term art radio project The Stadium Broadcast, which was staged in November 2014 in an earthquake-damaged sports stadium in Christchurch, New Zealand. Thousands of buildings and homes in Christchurch have been demolished since the February 22, 2011, earthquake, and by the time of the broadcast the stadium at Lancaster Park had been unused for three years and nine months, and its future was uncertain. The Stadium Broadcast constructed a radio memorial to the Park's 130-year history through archival recordings, the memories of local people, observation of its current state, and a performed site-specificity. The Stadium Broadcast reflected on the spatiality of radio sounds and transmissions, memory, postdisaster transitionality, and the impermanence of place.